Расчет колебаний и ресурса трубопровода маслосистемы газоперекачивающего агрегата - Белоцерковский, Александр Борисович; Жовдак, В. А.; Левашов, В. А.; Трубаев, Александр Иванович (НТУ "ХПИ", 2001)
The average time before fracture due to fatigue damage accumulation in spatial piping systems under kinematical excitation is determined. It is supposed that all supports of the piping system subjected to the identical acceleration modeling stationary random process. The solution of this problem is based on the finite element method and the spectral method. The computer program for IBM PC on the basis of this algorithm has been developed.
Keywords: трубопроводные системы; усталостные повреждения; кинематические воздействия; динамические характеристики; теория случайных функций; Турбо Паскаль